Effects of Polyhalogenated Aromatic Compounds on Porphyrin Metabolism - Hill, Robert H. (Environmental health perspectives, 1985)
Heme production is a vital metabolic process that occurs in the bone marrow and liver. Porphyrins are unused by-products of this biosynthetic process and normally occur in urine and other body fluids in low concentrations. Various disorders can disrupt the heme biosynthetic process, causing greater quantities of porphyrins in urine. The porphyrias are a group of diseases characterized by excessive porphyrins and other precursors in urine. Porphyrias may be either hereditary or acquired through exposure to certain drugs or chemicals. Porphyria cutanea tarda (PCT) is the disease associated with exposure to polyhalogenated aromatic compounds. The urinary porphyrin pattern is of great value in diagnosing PCT and defining the etiology of the disease. As this liver disease from chemical damage develops, the urinary pattern progressively changes. With the development of a rapid and sensitive high-performance liquid chromatography analysis, urinary porphyrin patterns can be easily monitored. All free porphyrin acids can be quantitatively analyzed in less than 15 min. In our studies of groups exposed to porphyrinogenic chemicals, we have not observed clear differences in the urinary porphyrin patterns of cases when compared with carefully selected controls. In animal studies, however, PCT was clearly associated with polybrominated biphenyl exposure. Future evaluation of the utility of urinary porphyrin patterns as a diagnostic tool will require a cohort that has received a recent, well-documented exposure and a comparable control population. Assay of erythrocyte uroporphyrinogen decarboxylase activity will also be needed to define the form of the PCT.